(untitled) (Research, Society and Development, 2022)
Introduction: Interstitial lung diseases (ILD) present similar clinical characteristics such as dyspnea and exercise intolerance. These characteristics are accentuated during physical exertion, although this has not yet been investigated in depth in this population. Aims: To compare the subjective sensation of dyspnea and fatigue by workload during exercise testing (ET) between patients with ILD and healthy subjects. Methods: The individuals performed the CPET on a cycle ergometer with an incremental protocol. At each stage of the test, the sensation of exertion was collected using the Borg scale of dyspnea (D) and fatigue (F). The slopes of the D and F curves by stage in the test were compared using linear regression using the Zar method (F test). Results: 37 patients with ILD and 29 controls were studied. The ILD group had a lower maximum load (60[40-80] vs healthy 120[100-160]; (P<.0001) and greater symptoms at the end of the test for D (P=0.02), but not for F (P=0.23) when compared to the control. Also, the ILD group presented more symptoms per watt (i.e. Borg/Watts) in ET compared to the control group for D (8x10-2±7x10-2 vs 2x10-2 ± 2x10-2; P=0.0007), and F (1x10-1± 9x10-2 vs 3x10-2 ± 1x10-2; P=0.001). D and F symptoms per watt (P<0.05 between curves). Conclusion: Patients with ILD have lower maximal exercise capacity and appear to have a more pronounced increase in D and F sensation per workload during ET.